2013
DOI: 10.1103/physrevlett.111.030501
|View full text |Cite
|
Sign up to set email alerts
|

Device-Independent Entanglement Quantification and Related Applications

Abstract: We present a general method to quantify both bipartite and multipartite entanglement in a device-independent manner, meaning that we put a lower bound on the amount of entanglement present in a system based on the observed data only but independent of any quantum description of the employed devices. Some of the bounds we obtain, such as for the Clauser-Horne-Shimony-Holt Bell inequality or the Svetlichny inequality, are shown to be tight. Besides, device-independent entanglement quantification can serve as a b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
349
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 173 publications
(354 citation statements)
references
References 59 publications
4
349
1
Order By: Relevance
“…Note that this definition was already used in Ref. [7] to quantify genuine multiparticle entanglement in a device independent manner.…”
Section: Modifying the Definition Of The Genuine Multiparticle Negatimentioning
confidence: 99%
See 1 more Smart Citation
“…Note that this definition was already used in Ref. [7] to quantify genuine multiparticle entanglement in a device independent manner.…”
Section: Modifying the Definition Of The Genuine Multiparticle Negatimentioning
confidence: 99%
“…[6], the GMN quantified how quantum reservoir engineering can create entangled states in cascaded quantum-optical networks driven by dissipative processes. Finally, it has been shown how the GMN can be measured experimentally in a device-independent way [7]. All these applications are based on the fact that the GMN can directly be computed, but this may also lead to the impression that the GMN is mainly a numerical tool and not accessible to an analytical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This possibility, unique to Bell inequalities, has been called deviceindependent certification. The first task to be studied this way was quantum key distribution [6]; it was followed by the task of generating certified randomness [7,8] and by the quantifications of some entanglement measures [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding statistics of the measurement outcomes is called a Bell correlation. It has been shown that the dimension and the entanglement of the underlying quantum state can be quantified in a device-independent way using only the Bell correlation data [5,[8][9][10]. In fact, some quantum states can even be pinned down completely by their violations of particular Bell inequalities, but this is only known to be possible for some special cases [1][2][3][4][15][16][17].…”
mentioning
confidence: 99%